Kajian Fenologi Perbungaan Anggrek Merpati (Dendrobium crumenatum Sw.) di Limau Manis Padang, Sumatra Barat - Suci Rahma Nita; Syamsuardi Syamsuardi; Mansyurdin Mansyurdin (Jurnal Biologi Universitas Andalas, 2015)
Pigeon orchid is one of epiphytic wild orchids and very important species in the genus Dendrobium. Flowering phenology of this species is still unclear. The purpose of this study was to describe flowering phenology of pigeon orchid. The study was conducted in Limau Manis Padang, West Sumatera and has been done from May until October 2015. Some aspects of flowering phenology such as the phase of flowers, flowering period, rainy time and stigma receptivity were observed. The results of this research  indicated that pigeon orchid flowering was induced by dicreasing of the temperature after rain. Flowers development consist of six phases from bud phase to be wilt with a span of 14 days and sometime stigma has begun receptive before the anthesis but optimal stage of stigma receptivity pigeon orchid occurs during anthesis.Key word: Phenology, pigeon orchid, stigma reseptivity.